تجدید دین سے متعلق علماء کی آراء کا تحقیقی جائزہ: A Research Analysis of Scholars Opinion on Reformation - Fayaz Muhammad; Dr. Sami ul Haq (Al Manhal Research Journal, 2023)
Renovation in religion means to restore the religion of Islam in its original form and shape as it was in the days of the Prophet ﷺ and his Companions. Renovation does not mean to invent something new on the basis of reason without sticking to Islamic principles this is called innovation.Three things are related to Quran and Hadiths. Renovation is impossible in the words of Quran because Allah Almighty has taken the responsibility that it cannot be changed No sort of distortion can be made in it people have started meanings of the Quran and Ahadith which are incorrect. To correctly interpret the Quran and Ahadith and to remove the distortion in meaning which is committed by people is named renovation. In Ahadith renovation means to secure them and to separate authentic from the ones which are unauthentic. In this way people restart action upon parts of the Quran and hadith which they stopped action upon, doing this practically is called renovation.